MODEL KURIKULUM DAN RELEVANSINYA DALAM KEHIDUPAN SEHARI-HARI DI MI WAHID HASYIM - Pujarisma, Litfia; Rahmawati; Andi Prastowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article reveals the results of research on the curriculum model and its relevance in daily life, where the curriculum is a concept in every learning. The use of the curriculum at Madrasah Ibtidaiyah (MI) Wahid Hasyim is currently still using 2 curricula in the learning process, namely: (1) Curriculum 2013 for grades 2, 3, 5 and 6; and (2) Independent Curriculum for grades 1 and 4. In this application, of course, it is the embodiment of the principle of relevance, the principle of flexibility, the principle of continuity, the principle of practicality and the principle of effectiveness. These curriculum principles are of course the basis of goals or guidelines in every process of teaching and learning activities at Madrasah Ibtidaiyah Wahid Hasyim. So that learning at MI Wahid Hasyim can strive with the existing curriculum principles. This study uses case study research that focuses on qualitative. Qualitative research carried out is by observation and interviews to find out an existing event. In this study, the researcher conducted research directly at the Madrasah Ibtidaiyah Wahid Hashim school. Then the interviewer is a representative of the madrasah of the curriculum section as well as the homeroom teacher of class 5B. It is hoped that this research will be able to provide benefits to the general public about the curriculum model and its relevance in daily life.